Impact of an added milk intervention to a micronutrient fortified school feeding program on child diet, cognition, learning, nutritional status, school attendance, and health: Statistical analysis plan - Bliznashka, Lilia; Gelli, Aulo (BioMed Central, 2024)
Even before the onset of the current civil war, Yemen was one of the poorest countries in the world ranking 183 out of 191 countries and territories on the UN Human Development Index. The World Food Programme (WFP) estimates that currently 17 million Yemeni (half the population) are food insecure and 2.2 million preschool children are acutely malnourished (World Food Programme, 2023a). In 2022, 17% of school children in Yemen received school meals (WFP, 2022) and in 2023, the humanitarian response will cover only 8% of the needs of education sector, leaving it with the second highest unmet need (OCHA, 2023). WFP provides nutritious snacks (imported or locally procured), either fortified date bars or fortified high energy biscuits, to 1.55 million school children. There is an urgent need to understand how to improve access to nutritious school meals to support students and schools throughout the country.